PENELUSURAN ARSITEKTUR INDIS PADA STASIUN KERETA API BINJAI - Hartono, Ludy; Pane, Imam Faisal (Talenta Publisher, 2017)
The colonial’s architecture was spread in cities in Indonesia. It was influenced by the modern architecture that was emerging in Europe. For the time being, acculturation happened between the Dutch and the heterogeneous Indonesian. Its design adapted with the local condition and climate. Mostly, it is called by Indis Architecture. It was the result of the culture and lifestyle which was begun since the Dutch colony. As for example, Binjai Railway Station, which was established in 1887. This adapted two different culture, the Dutch and the Malays. This research describes Indis architecture in Binjai Railway Station by qualitative methods and descriptive approach. Data will be taken by observing form and architectural element of the building. As of it, Binjai Railway Staion adapted two different cultures which resulted in a new culture, Indis architecture.